2018
DOI: 10.1089/jir.2017.0088
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Interleukin-1β in Post-Traumatic Stress Disorder: Evidence from Human and Animal Studies

Abstract: Pro-inflammatory cytokines, such as interleukin (IL)-1β, have been implicated as underlying pathophysiological mechanisms and potential biomarkers of post-traumatic stress disorder (PTSD). This systematic review examines data regarding IL-1β production/concentration in human and animal studies of PTSD. In accordance with PRISMA guidelines, relevant articles from PubMed were reviewed from inception until July 10, 2017. Nineteen studies were eligible for inclusion. Animal studies demonstrated increased hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 61 publications
(77 reference statements)
0
16
0
Order By: Relevance
“…Our findings are in accordance with some, but not all previous research. Studies have found PTSD symptoms to decrease over time, 10 with increasing IL-1β levels, 21 but also with decreasing IL-1β levels. 22 Increasing levels of TNF-α have also been found despite decreasing symptom severity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are in accordance with some, but not all previous research. Studies have found PTSD symptoms to decrease over time, 10 with increasing IL-1β levels, 21 but also with decreasing IL-1β levels. 22 Increasing levels of TNF-α have also been found despite decreasing symptom severity.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory agents have been suggested to reduce IL-1β and play a role in future treatment of PTSD. 10 , 29 We analyzed anti-inflammatory drug use in the patient sample in general to get an impression of overall levels and development of inflammatory markers. We found a higher level of IL-1β in those using anti-inflammatory drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, evidence has shown that cytokines play an important role in mental health and the pathophysiology of mental disorders, including disorders which are highly comorbid with EDs such as depression (Dowlati et al, 2010;Lichtblau et al, 2013), anxiety disorders (Baldwin et al, 2017;Quagliato and Nardi, 2017), post-traumatic stress disorder (Hussein et al, 2017;Waheed et al, 2018), and sleep disorders (Weschenfelder et al, 2012). Cytokines have also been linked with body weight and its regulation (Fonseka et al, 2016); for example, plasma levels of pro-inflammatory cytokine IL-6 have been shown to correlate positively with body mass index (BMI) (Himmerich et al, 2006;Schmidt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the variety of diagnoses may explain a wide spread in cytokine levels in our study population. It has been suggested that anti-inflammatory drugs may play a role in outcome of PTSD by altering neuro-immune processes (Miller et al, 2018;Waheed et al, 2018) and thus contribute to mental recovery. Among those not using anti-inflammatory drugs, the PTSD patients had significantly higher GSI levels than non-PTSD patients.…”
Section: Discussionmentioning
confidence: 99%